Interleukin‐6 limits influenza‐induced inflammation and protects against fatal lung pathology. Issue 10 (12th August 2013) - Lauder, Sarah N.; Jones, Emma; Smart, Kathryn; Bloom, Anja; Williams, Anwen S.; Hindley, James P.; Ondondo, Beatrice; Taylor, Philip R.; Clement, Mathew; Fielding, Ceri; Godkin, Andrew J.; Jones, Simon A.; et al.
<x xml:space="preserve">Abstract</x> Balancing the generation of immune responses capable of controlling virus replication with those causing immunopathology is critical for the survival of the host and resolution of influenza‐induced inflammation. Based on the capacity of interleukin‐6 (IL‐6) to govern both optimal T‐cell responses and inflammatory resolution, we hypothesised that IL‐6 plays an important role in maintaining this balance. Comparison of innate and adaptive immune responses in influenza‐infected wild‐type control and IL‐6‐deficient mice revealed striking differences in virus clearance, lung immunopathology and generation of heterosubtypic immunity. Mice lacking IL‑6 displayed a profound defect in their ability to mount an anti‐viral T‐cell response. Failure to adequately control virus was further associated with an enhanced infiltration of inflammatory monocytes into the lung and an elevated production of the pro‐inflammatory cytokines, IFN‐α and TNF‐α. These events were associated with severe lung damage, characterised by profound vascular leakage and death. Our data highlight an essential role for IL‐6 in orchestrating anti‐viral immunity through an ability to limit inflammation, promote protective adaptive immune responses and prevent fatal immunopathology.